Innovative Economic Technologies and Policies in the Energy Sector - Borodin, Alex (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a Special Issue titled "Innovative Economic Technologies and Policies in the Energy Sector" that was published in Energies.